PENGARUH LIKUIDITAS, LEVERAGE, DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Utami, Widya Ayu; Ramdhansyah, Ramdhansyah (Jurnal Akuntansi AKTIVA, 2026)
A higher level of trust and capital market competitiveness is often associated with highly valued companies. An important indicator that reflects how investors feel about a business's current and future prospects is its company value. This study aims to analyze manufacturing companies listed on the Indonesia Stock Exchange from 2022 to 2024 with a focus on their sales growth, leverage, and liquidity to evaluate their firm worth. Based on secondary data culled from financial records, the study employs a quantitative technique and employs purposive sampling to choose its sample. Several methods for analyzing the data were used, including descriptive statistics, conventional assumption tests, and SPSS version 26 multiple linear regression analysis. The results demonstrate that the value of a company is greatly affected simultaneously by sales growth, leverage, and liquidity. Firm value is positively and significantly affected by liquidity and leverage, but not by sales growth. Accordingly, investors consider a company's financial health with sales growth as a measure of its business value.